Encouraging civil servants to be frank and fearless: Merit recruitment and employee voice - Cooper, Christopher A. (2018)
Recruiting civil servants on the basis of merit is believed to improve the quality of governance because it increases the bureaucracy's expertise, leads bureaucrats to develop distinct preferences and encourages them to candidly voice their opinions to others. Yet, to date, the reason why merit recruitment positively affects employee voice remains theoretically vague and has received little empirical scrutiny. This article advances this research by theoretically specifying why merit recruitment positively affects employee voice, and by empirically testing this association with survey data measuring the perceptions of federal civil servants in Canada. Controlling for several additional factors believed to influence employee voice, the results from various multivariate regression models show a robust and statistically significant association between merit recruitment and fear to voice a dissenting opinion. The more civil servants believe that merit recruitment is high, the less they fear reprisal for expressing a dissenting opinion to their superiors. - Reproduced.
Keywords: Personnel, Public - Recruiting